Design and evaluation system construction of VR cultural heritage products from the perspective of user experience - Liu, Yuyuan (International Scientific Technical and Economic Research, 2025)
In the digital age, virtual reality (VR) technology offers innovative avenues for cultural heritage preservation, but its development still faces a disconnect between user experience and the transmission of cultural values. This paper systematically constructs a design and evaluation system for VR cultural heritage products from a user experience perspective. First, by analyzing the connotations and types of VR cultural heritage products and integrating user experience theory with cultural communication theory, a design framework is proposed with the core goal of "integrating cultural value transmission with deep user experience." This multi-layered design strategy encompasses strategic, content, interaction, and sensory layers. Second, a comprehensive evaluation model is established encompassing four dimensions: system usability, experience quality, emotion and cognition, and behavioral intention. This model integrates subjective and objective evaluation methods to form a closed-loop optimization mechanism. Finally, implementation recommendations are proposed for typical application scenarios such as museum guided tours, intangible cultural heritage teaching, and historical restoration. This study aims to provide theoretical guidance and practical tools for the development of VR cultural heritage products, promoting their transformation from a technology-oriented to a user-value-oriented approach.